Мобільність автомобіля в умовах бездоріжжя - Хома, Віталій (ТзОВ «Галицька видавнича спілка», 2021)
The article describes the boundary conditions of transportation on dirt roads and off-road
Road mobiliy in off-road contitions
Keywords: 656.13